The use of the normal tissue non-complication probability (NTCP0) in the safety evaluations as a new alternative of assessing the side-effects of the radiation oncology treatments. (3rd April 2023) - Frometa-Castillo, Terman; Pyakuryal, Anil; Narayanasamy, Ganesh; Wals-Zurita, Amadeo; Mesbahi, Asghar
Abstract: Purpose: To encourage the use of the NTCP0 for evaluating safety as a new alternative of assessing the S-Es of the radiation oncology treatments; and the use of the 'NTCP0cal' methodology that calculates/estimates NTCP0. Method: Revisions of studies related to use of the NTCP in the evaluations of S-Es. Development of the first version of the Matlab application of our methodology, which provides three options, two of them employ the well-known aspects of a phenomenological model, or the relationship with the TNTCP; where NTCP0 = 100%-TNTCP; and the third option determines NTCP0 from an assumed NTCP discrete probabilistic distribution from the binomial distribution, where one of its parameters is automatically defined from a databased of the Disease locations Vs. Late complications. Result: As result of revisions of some QUANTEC studies, we can say that: (1) The majority of current NTCP models are DVH-based; (2) The risk of toxicity is the way of evaluating the S-Es of the radiation oncology treatments; and (3) The NTCP are used mainly for evaluations of individual or principal complications or Endpoints of the radiation treatments. The 'NTCP0cal' Matlab application developed in this study has three calculation options. Two of the options provide additional graphical information about the distributions. Conclusions: The NTCP0 is a new radiobiological concept, its introduction let to correct some current P + and UTCP formulations, and will allow evaluating S-Es in whatever activity involving ionizing radiation, like radiation treatments; and its phenomenological model function of dose prescribed (D = n*d) will allow calculating values of NTCP0 for a range of dose per fraction (d) in a treatment with a determined number of fractions (n), or for range of n for a constant d . The DVH is irrelevant for this model. For whatever radiation treatment given to a population of similar patients under similar circumstances, the NTCP0 is calculated as ratio of the number of patients without acute/late complications and total of them. When this number is unknown, then NTCP0 can be obtained using the 'NTCP0cal' application.